2021
DOI: 10.3390/cancers13020352
|View full text |Cite
|
Sign up to set email alerts
|

Predicting of Sentinel Lymph Node Status in Breast Cancer Patients with Clinically Negative Nodes: A Validation Study

Abstract: In the absence of lymph node abnormalities detectable on clinical examination or imaging, the guidelines provide for the dissection of the first axillary draining lymph nodes during surgery. It is not always possible to arrive at surgery without diagnostic doubts, and machine learning algorithms can support clinical decisions. The web calculator CancerMath (CM) allows you to estimate the probability of having positive lymph nodes valued on the basis of tumor size, age, histologic type, grading, expression of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…We further analyzed the clinicopathological characteristics of these 31 patients and found that HER2 status (p<0.03) and Ki67 (p<0.02) were significant factors affecting the accuracy rate of the number of positive SLNs ( Table 5 ). Fanizzi et al 23 found that the prognostic factors HER2 and Ki67 can help to improve the predictive performance of the CancerMath (CM) model for SLN positive. These results suggest that the HER2 positive and the high expression of Ki67 may be associated with SLN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…We further analyzed the clinicopathological characteristics of these 31 patients and found that HER2 status (p<0.03) and Ki67 (p<0.02) were significant factors affecting the accuracy rate of the number of positive SLNs ( Table 5 ). Fanizzi et al 23 found that the prognostic factors HER2 and Ki67 can help to improve the predictive performance of the CancerMath (CM) model for SLN positive. These results suggest that the HER2 positive and the high expression of Ki67 may be associated with SLN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the state-of-the-art, there are a number of works that make use of predictive models or radiomic analysis to identify and characterize breast neoplasms and the state of lymph node involvement [ 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, as showed by experimental results by Fanizzi et al, CancerMath is not particularly suitable for use as a support instrument for the prediction of metastatic lymph nodes on clinically negative patients. And again, it should be emphasized that those tools are not validated in patients after PST, which is the target group of our study [ 30 ].…”
Section: Discussionmentioning
confidence: 99%